The Role of Environmental, Social, and Governance (ESG) Disclosure on Firm Value in ASEAN - Mahedi Hasan (PT Advanced business journal, 2025)
This study investigates the impact of Environmental, Social, and Governance (ESG) disclosures on firm value within ASEAN markets, addressing a critical gap in understanding how non-financial reporting influences corporate performance in emerging economies. Employing a quantitative cross-sectional design, the research analyzes ESG disclosures from publicly listed firms across major ASEAN economies. Regression analysis and endogeneity controls are applied to assess correlations between ESG scores and firm value indicators such as market capitalization and return on assets (ROA). Preliminary results reveal a positive association between ESG disclosure quality and firm performance, particularly in sectors with stringent regulatory oversight. Governance factors, including board diversity and ethical management, significantly enhance firm value. However, inconsistencies in disclosure practices across industries and countries underscore the need for standardized ESG frameworks. The study's cross-sectional nature limits long-term causal inference. Future research should adopt longitudinal methods and include private firms to broaden applicability. Sectoral and cultural nuances also warrant deeper exploration to refine ESG strategies in ASEAN. The findings offer actionable insights for policymakers, investors, and corporate leaders, advocating for improved transparency and standardized ESG reporting to foster sustainable growth and investor confidence in ASEAN markets. By contextualizing ESG disclosures within ASEAN’s socio-economic and cultural landscape, this study contributes a localized perspective to the global ESG discourse, highlighting the strategic importance of sustainability reporting in enhancing firm value.